Assessment of dental caries and oral hygiene status among twins - Priya Subramaniam; K L Girish Babu; Bharath Vardhana (Wolters Kluwer Medknow Publications, 2018)
The study of twins provides a unique opportunity to evaluate the genetic and nongenetic contributions to a variance of multitude of traits. Twin research has revealed the impact of a strong genetic component to the variance of many dental traits. The present study was conducted to assess the dental caries and oral hygiene status in monozygotic (MZ) and dizygotic (DZ) twins. A random sample of 129 MZ and DZ twin pairs aged 6-15 years were included in this study. The zygosity of twin pairs was initially recorded by facial appearance and later determined by dermatoglyphics. Dental caries and oral hygiene status were recorded in these twin pairs and the data were subjected to statistical analysis. No significant difference was observed in the mean decayed, extracted due to caries and filled teeth (deft) in primary dentition and decayed, missing and filled (DMFT) in permanent dentition scores and oral hygiene status in MZ and DZ twin pairs. The similarity observed in oral health status reflects the effects of a shared environment in MZ and DZ twin pairs.